2008
DOI: 10.1161/hypertensionaha.107.101725
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile but Not Steady Component of Blood Pressure Predicts Cardiovascular Events in Coronary Patients

Abstract: Abstract-Although the differences between central and peripheral blood pressure (BP) values have been known for decades, the consequences of decision making based on peripheral rather than central BP have only recently been recognized. There are only a few studies assessing the relationship between intraaortic BP and cardiovascular risk. In addition, the relationship between central BP and the risk of cardiovascular events in a large group of coronary patients has not yet been evaluated. Therefore, the aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
143
2
11

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(164 citation statements)
references
References 34 publications
(58 reference statements)
5
143
2
11
Order By: Relevance
“…14,26,30 Although all current noninvasive methods for the estimation of aortic pressure are affected by the limited accuracy of the oscillometric blood pressure monitors, 31,32 the clinical values of the central blood pressure estimates remain evident. 5,7,8 Because brachial SBP2 represents a very significant weight in both the invasive and noninvasive prediction models, the accurate identification of SBP2 on a peripheral pulse without visible late systolic peak may deserve concerns. The identification of SBP2 on a radial pressure waveform may be difficult when it is close to the end-systolic pressure as with nitroglycerin, in youth, with tachycardia, and in systolic heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,26,30 Although all current noninvasive methods for the estimation of aortic pressure are affected by the limited accuracy of the oscillometric blood pressure monitors, 31,32 the clinical values of the central blood pressure estimates remain evident. 5,7,8 Because brachial SBP2 represents a very significant weight in both the invasive and noninvasive prediction models, the accurate identification of SBP2 on a peripheral pulse without visible late systolic peak may deserve concerns. The identification of SBP2 on a radial pressure waveform may be difficult when it is close to the end-systolic pressure as with nitroglycerin, in youth, with tachycardia, and in systolic heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The discrepancy between the central and peripheral blood pressures is mainly caused by the central-to-peripheral amplification of the pressure pulse and may magnify with administration of vasoactive agents. [2][3][4] Furthermore, recent evidence from epidemiological studies, 5,6 clinical observation, 7 and a large clinical trial 8 suggest that central blood pressure is more relevant than peripheral blood pressure in predicting target organ damage and cardiovascular outcomes. However, the implementation of central blood pressure in the daily practice of hypertension management may require the availability of its reliable measurements to both medical care providers in the clinics and patients at home.…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate and b-blocking agents (yes/no) were used as conventional factors potentially acting independently on PP. [1][2][3][4][5] According to the degree of significance (Po0.15), the variables were either added or not added in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Brachial non-invasive SBP, DBP or PP levels gave even less indications on the predictive value of coronary alterations. Interestingly, Jankowski et al 2 have recently demonstrated that aortic PP was the most important predictor of CV events in coronary patients with preserved as well as in those with reduced EF. Because, in the present population of old hypertensive and atherosclerotic subjects, the increased PP is due to a low DBP with SBP close to normal values, the corresponding patients are often clinically classified as 'adequately controlled' (SBP o140 mm Hg and DBP o90 mm Hg) by antihypertensive drug treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation